Prenatal, Perinatal, and Other Risk Factors of Attention-Deficit Hyperactivity Disorder in Soerojo Hospital - Sutanto, Doddy BL; Sevriana, Ery Surya; Pangestuti, Rayi Citra Ayu; Hanifa, Yumna Nur Millati; Bangun, Susi Rutmalem (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Long-term negative effects on academic ability and social activities can persist into adulthood in children with neurodevelopmental disorders characterized by inattention, hyperactivity, and impulsivity (Attention Deficit Hyperactivity Disorder/ ADHD). Genetic, neurotransmitter, neurological, environmental, psychosocial, brain trauma, and addictive factors are some of the predisposing factors for ADHD. But theoretically, maternal risk factors often contribute to neuropsychiatric disorders, because of their potential influence on child brain development. This study aimed to assess the proportion of maternal risk factors consisting of prenatal, perinatal, and other factors of ADHD in Soerojo Hospital. Subjects and Method: A descriptive-analytic study with a retrospective approach was conducted on April-June 2022 at Soerojo Hospital. A total of 90 subjects pediatric patients diagnosed with ADHD selected by purposive sampling. The data were collected using questionnaires. The data were described in frequency (n) and percent (%). Results: The proportion of prenatal risk factors are mother’s age at pregnancy (19%), maternal disease history (8%), hormonal contraception pre-pregnancy (24%), maternal psychopathology (34%), maternal excess weight (49%); the proportion of perinatal risk factors are premature birth (12%), operative abdominal and vaginal delivery (49%), low birth weight (13%), neonatal emergencies (34%); while other factors are hereditary factors (13%), exposure to cigarettes (47%), and marital conditions (23%). Conclusion: The most common maternal risk factors were maternal excess weight, operative abdominal and vaginal delivery, exposure to cigarettes, maternal psychopathology, and neonatal emergencies. Keywords: ADHD, maternal risk factor, prenatal, perinatal. Correspondence: Doddy Sutanto, Department of Obstetric and Gynecology, Soerojo Hospital, Magelang, Indonesia, Jl. Ahmad Yani No. 169, Magelang 56115, Central Java. Email: doddysutanto.soerojohospital@gmail.com.